Pengembangan Aplikasi Presensi Berbasis RFID untuk Meningkatkan Disiplin Peserta Didik di SMP Negeri 7 Madiun - Setyaningrum, Reti; Mohammad Syahidul Haq; Mufarrihul Hazin; Amrozi Khamidi (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to develop an RFID-based attendance application system to improve student discipline at SMP Negeri 7 Madiun, especially in school attendance and congregational Duhur prayer activities. The research method used is the Research and Development (R&D) model from Borg and Gall which consists of ten procedural stages, starting from preliminary studies to product implementation. The results of the study indicate that the previous manual attendance system was less effective and efficient because it did not record attendance times accurately and was at risk of losing data. With the implementation of an RFID system supported by NodeMCU ESP8266 and smartcards as attendance cards, a system is obtained that is able to record attendance automatically, accurately, and in real-time. Teachers, parents, and students can easily monitor attendance data through the system. The conclusion of this study is that the RFID-based attendance system is able to maximize attendance recording, facilitate the management of attendance data, and improve student discipline both in learning activities and the formation of religious character.                                                                                                                                    Keywords: Student Discipline, RFID, Educational Information System, Digital Attendance